Efficacy of Montelukast for Prevention of Upper Respiratory Tract Infection in Children: A Randomized, Placebo-Controlled Trial - Dorreh, Fatemeh; Esmaili, Mohammad Hasan; Yousefhajian, Parsa; Naziri, Mahdieh; Eghbali, Aziz; Bagheri, Bahador (Pharmaceutical Sciences, 2020)
Background: Upper Respiratory tract infection (URTI) or common cold is very prevalent in children particularly in young children. Leukotriene receptor antagonists (LTRAs) like montelukast are effective drugs in asthma and some other respiratory diseases. Our purpose was to study preventive effects of montelukast on pediatric URTI. Methods: This randomized, placebo-controlled, and double blind trial was performed on 450 healthy children aged 1-5 year in Amir Kabir Hospital, Arak, Iran. Children were randomized 1:1 to placebo group or montelukast group for 12 weeks. Number of URTI episodes and duration were the primary end points and were compared at baseline and after termination of treatment. Results: Mean age was 28 ± 12.3 months. Mean of URTI episodes was 0.7 ± 0.57 in children treated with montelukast and 1.27 ± 0.72 in children treated with placebo, respectively. Differences were statistically significant (P =0.01). A significant difference was seen in URTI duration between two study groups (6.3 ± 6.1 vs 4.1 ± 3.9, P = 0.05). In addition, duration of fever was shorter in children receiving montelukast (P=0.001). Conclusion: Our study indicates that 3 month treatment with montelukast is effective for reducing the incidence of URTI in young children. This treatment has an acceptable safety without any serious concern.